Lip, oral cavity and pharyngeal cancers in the population of the city of Belgrade in the period 1999-2010 - Videnović Goran; Ilić Danijela; Miljuš Dragan; Krasić Dragan; Vlahović Zoran; Živković Snežana; Pavlović Aleksandar (Vojnosanitetski Pregled)
Background/Aim. Cancers of the lip, oral cavity and pharynx (LOCP) are frequently grouped together mainly because they have similar risk factors. The incidence rate of these cancers varies worldwide depending on the geographic location. The aim of this study was to determine trends in age-standardized incidence rates of LOCP cancers in the Belgrade population during a 12-year period, from 1999 to 2010. Methods. From The Serbian Cancer Registry (The Registry), we extracted all cases of LOCP cancers registered in Belgrade from January 1, 1999 to December 31, 2010. Joinpoint regression analysis was used to define trends and annual percentage change (APC). Results. A total number of 2,025 (1,509 in men and 516 in women) LOCP cancers were reported to the Registry during the study period. The age standardized rate (ASR) for the entire period and for all LOCP cancers, was 6.24 per 100,000 persons (10.35 for men and 2.86 for women). ASR for lip cancers decreased (p < 0.001) during the study period with APC of -8.4%. The ASR for oral cavity and pharyngeal cancers increased (p < 0.05). Conclusion. Our results show a significantly decreasing trend of the incidence rate for lip cancers in the population of the city of Belgrade between 1999 and 2010. On the contrary, the incidence of oral cavity and pharyngeal cancers increased for both men and women.